Role of CD44 and CD8 in Colorectal Adenocarcinoma metastatic - Baiq Ratna Kumaladewi; Willy Sandhika; Heryawati Heryawati (Medical Laboratory Technology Journal, 2020)
Colorectal adenocarcinoma is one of the most prevalent malignancies worldwide. The presence of regional lymph node metastases is an important prognostic indicator in colorectal adenocarcinoma. CD44 is a transmembrane protein and a cancer stem cell biomarker that plays a role in tumor proliferation, metastasis, and recurrence. The tumor microenvironment has a vital role in the stage of tumor development. CD8 is one of microenvironment's component which kills the tumor cells. This study aimed to analyze the expression of CD44 and CD8 and investigated their association with colorectal adenocarcinoma metastatic. This study's benefit is that the resulting study can be used as a prognostic factor in colorectal adenocarcinoma. This study included 56 paraffin blocks of patients diagnosed as colorectal adenocarcinoma during January 2017-December 2018 in Anatomic Pathology Laboratory Dr. Soetomo Hospital Surabaya. The paraffin blocks were sliced and stained with immunohistochemistry for CD44 and CD8. The parameters were a positive percentage of tumor cell and lymphocyte immunoreactivity against CD44 and CD8 antibodies. The percentage of CD44 is higher in the metastatic group, and the percentage of CD8 is higher in the non-metastatic group. There was a significant negative correlation between CD44 and CD8 expression in regional lymph nodes metastatic. These results indicated that CD44 and CD8 have a vital role in the incidence of metastasis.